Negative electrode for rechargeable lithium battery and rechargeable lithium battery including same
By introducing a bonding layer of high-content carbon-based material into the negative electrode of the rechargeable lithium battery, the problem of separation of the negative electrode active material layer during the charging and discharge cycles is solved, and the cycle life characteristics of the battery are significantly improved.
Patent Information
- Application Number
- CN202410956035.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-08-17
- Filing Date
- 2024-07-17
- Publication Date
- 2025-02-21
AI Technical Summary
The separation of the active material layer in the negative electrode of the existing rechargeable lithium battery during the charging and discharging cycles leads to poor cycle life characteristics.
A thin adhesive layer is introduced between the current collector and the negative electrode active material layer. The adhesive layer is composed of high carbon content and has high interface adhesion to enhance the adhesion of the two.
By introducing an adhesive layer with a high content of carbon-based materials, the separation of the negative electrode active material layer is effectively suppressed or reduced, and the cycle life characteristics of the rechargeable lithium battery are improved.
Smart Images

Figure CN119495709A_ABST
Abstract
Description
Technical Field
[0001] Embodiments of the present disclosure relate to a negative electrode for a rechargeable lithium battery and a rechargeable lithium battery including the negative electrode. Background Art
[0002] Rechargeable lithium batteries are batteries that exhibit excellent discharge voltage and high energy density.
[0003] Such a battery includes a positive electrode, a negative electrode, and an electrolyte, and the electrodes (such as the positive electrode and the negative electrode) include a current collector and an active material layer on the current collector. Summary of the invention
[0004] One or more embodiments of the present disclosure provide a negative electrode for a rechargeable lithium battery that exhibits good interfacial adhesion between a current collector and an active material layer.
[0005] One or more embodiments provide a rechargeable lithium battery including a negative electrode.
[0006] One or more embodiments provide a negative electrode for a rechargeable lithium battery, the negative electrode for a rechargeable lithium battery comprising: a current collector; a negative electrode active material layer; and an adhesive layer between the current collector and the negative electrode active material and having a thickness of about 30 μm or less, wherein the adhesive layer comprises a carbon-based material in an amount of about 90 wt % or more based on a total of 100 wt % of the adhesive layer.
[0007] One or more embodiments provide a negative electrode for a rechargeable lithium battery, the negative electrode for a rechargeable lithium battery comprising: a current collector; a negative electrode active material layer; and an adhesive layer between the current collector and the negative electrode active material, wherein the interfacial adhesion between the adhesive layer and the current collector and / or the interfacial adhesion between the adhesive layer and the negative electrode active material layer is about 5 gf / mm or greater.
[0008] Another embodiment provides a rechargeable lithium battery including a negative electrode, a positive electrode, and a non-aqueous electrolyte.
[0009] Other embodiments are included in the detailed description that follows.
[0010] The negative electrode according to one or more embodiments may have improved adhesion between a current collector and an active material layer, thereby improving cycle-life characteristics. BRIEF DESCRIPTION OF THE DRAWINGS
[0011] The drawings, together with the specification, illustrate embodiments of the presently disclosed subject matter, and, together with the description, serve to explain principles of the embodiments of the presently disclosed subject matter.
[0012] Figure 1 is a schematic diagram illustrating a negative electrode for a rechargeable lithium battery according to one or more embodiments.
[0013] Figure 2 is a diagram illustrating a method of preparing a negative electrode for a rechargeable lithium battery according to one or more embodiments.
[0014] Figure 3 is a schematic diagram illustrating a rechargeable lithium battery according to one or more embodiments. DETAILED DESCRIPTION
[0015] Hereinafter, embodiments are described in more detail. However, these embodiments are examples, and the present disclosure is not limited thereto, and the present disclosure is defined by the scope of the claims and their equivalents.
[0016] The terms used in the specification are used to explain the embodiments of the present disclosure and are not intended to limit the present disclosure.An expression in the singular includes an expression in the plural form unless the context clearly indicates otherwise.
[0017] As used herein, the term "combinations thereof" may include mixtures, laminates, composites, copolymers, alloys, blends, and reactants of the constituent parts.
[0018] As used herein, the terms "comprises," "includes," or "has" are intended to indicate the presence of the stated features, quantities, steps, constituent elements (components), or combinations thereof, but it should be understood that the possibility of the presence or addition of one or more other features, quantities, steps, constituent elements (components), or combinations thereof, is not precluded.
[0019] The drawings may show thickness exaggerated to clearly show the various layers and regions, and the same reference numerals are given to similar components throughout the specification. If an element such as a layer, film, region, plate, etc. is referred to as being "on" or "over" another component, this may include not only embodiments where it is "directly on" the other component, but also embodiments where another element exists therebetween. Conversely, if an element is referred to as being "directly on" another element, there are no intervening elements.
[0020] Here, the term "layer" includes a shape completely formed on the entire surface, or a shape formed on a part of the surface if viewed from a plan view.
[0021] Here, “or” is not to be interpreted as an exclusive meaning, for example, “A or B” is interpreted to include A, B, A+B, etc.
[0022] Unless otherwise defined in the specification, the particle diameter or particle size may be an average particle diameter. The average particle diameter represents an average particle diameter (D50) of about 50% by volume of the cumulative volume in the particle size distribution. The average particle diameter D50 may be measured by any suitable method used in the art (e.g., by a particle size analyzer, a transmission electron microscope image, and / or a scanning electron microscope image). In one or more embodiments, a dynamic light scattering measurement device is used to perform data analysis, and the number of particles is counted for each particle size range, whereby the average particle diameter (D50) value may be easily obtained by calculation, and / or the average particle diameter (D50) value may be easily obtained using a laser diffraction method.
[0023] The negative electrode for a rechargeable lithium battery according to one or more embodiments includes a current collector, a negative electrode active material layer, and a bonding layer between the current collector and the negative electrode active material layer. Since the bonding layer is between the current collector and the negative electrode active material layer, the bonding between the current collector and the negative electrode active material layer can be effectively increased.
[0024] like Figure 1 As schematically shown in FIG. 1 , the negative electrode 1 includes a current collector 3 , a binding layer 5 , and a negative electrode active material layer 7 , which are sequentially arranged. Figure 1 It is emphasized that the adhesive layer 5 is thinner than the negative electrode active material layer 7, and only the current collector 3 is shown, so it does not necessarily mean that Figure 1 The current collector 3 shown in FIG. 1 is a thin film thinner than the adhesive layer 5 and the negative electrode active material layer 7. For example, the relative thickness of the current collector 3 may be greater than Figure 1 The relative thickness shown in is large.
[0025] In one or more embodiments, the bonding layer may have a thickness of about 30 μm or less and may have about 90 wt% or more of carbon-based materials based on a total of 100 wt% of the bonding layer. In one or more embodiments, the bonding layer may include about 90 wt% to about 95 wt% of carbon-based materials based on a total of 100 wt% of the bonding layer.
[0026] Therefore, the thickness of the bonding layer is much thinner than the thickness of the active material layer. The thickness of the bonding layer may be about 30 μm or less, about 10 μm to about 30 μm, or about 15 μm to about 30 μm. If the thickness of the bonding layer is greater than 30 μm, the resistance will increase, and the ratio of the active material layer in the electrode will decrease, thereby reducing the capacity.
[0027] In one or more embodiments, the negative active material layer may have a thickness of about 30 μm to about 120 μm or about 50 μm to about 100 μm.
[0028] A thickness ratio of the binding layer to the negative active material layer may be about 1:1 to about 1:4 or about 1:1 to about 1:3.
[0029] When the bonding layer and the negative electrode active material layer can have a thickness within the thickness range described herein, if the thickness of the bonding layer and the negative electrode active material layer is greater than the range described herein, the adhesion of the bonding layer to the current collector and / or the adhesion of the bonding layer to the negative electrode active material can be more firmly maintained.
[0030] In one or more embodiments, the adhesive layer has excellent interfacial adhesion to the current collector, for example, the interfacial adhesion between the adhesive layer and the current collector may be about 5 gf / mm or greater. The interfacial adhesion between the adhesive layer and the current collector may be about 5 gf / mm to about 10 gf / mm. In one or more embodiments, the interfacial adhesion is very high, about 5 gf / mm or greater, indicating that the adhesive layer is well attached to the current collector, and therefore, the negative active material layer may be firmly attached through the adhesive layer.
[0031] Therefore, separation of the negative electrode active material layer during repeated charge and discharge cycles can be effectively suppressed or reduced, thereby improving cycle-life characteristics.
[0032] In one or more embodiments, the adhesive layer includes a carbon-based material and a first adhesive. For example, the adhesive layer may be composed of a carbon-based material and a first adhesive.
[0033] The carbon material may be crystalline carbon, amorphous carbon or a combination thereof. Crystalline carbon may be graphite such as natural graphite and / or artificial graphite in an indefinite shape, plate-like, flaky, spherical and / or fibrous form, and amorphous carbon may be soft carbon, hard carbon, mesophase pitch carbide and / or sintered coke, etc.
[0034] Therefore, the adhesive layer does not include Si-based materials. During charge and discharge, Si-based materials have more severe volume expansion than carbon-based materials, and therefore, including Si-based materials in the adhesive layer may result in reduced adhesion, so that the effect of improving adhesion by providing an adhesive layer between the current collector and the negative electrode active material layer may not be achieved. Therefore, it may not be appropriate, desirable, or suitable for the adhesive layer to include Si-based materials.
[0035] In one or more embodiments, the negative active material layer further includes a binder, for example, a second binder that is the same as or different from the first binder.
[0036] Based on the total 100wt% of the adhesive layer, the amount of the first binder may be about 10wt% or less, or about 3wt% to about 10wt%. Based on the total 100wt% of the negative electrode active material layer and the adhesive layer, the amount of the first binder may be about 5wt% or less, or about 1wt% to about 5wt%. If the amount of the first binder satisfies the range here, the adhesion can be further improved without (e.g., substantially) increasing the resistance.
[0037] The amount of the second binder may be about 3 wt % or less, or about 1 wt % to about 3 wt % based on 100 wt % of the total negative electrode active material layer. The amount of the second binder may be about 2.4 wt % or less, or about 1 wt % to about 2.4 wt % based on 100 wt % of the total negative electrode active material layer and the binding layer.
[0038] In one or more embodiments, the first binder may be the same as or different from the second binder.The binder may include a non-aqueous binder, an aqueous binder, or a combination thereof.
[0039] The non-aqueous binder may be ethylene propylene copolymer, polyacrylonitrile, polystyrene, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamideimide, polyimide, or a combination thereof.
[0040] The aqueous binder can be styrene-butadiene rubber (SBR), acrylated styrene-butadiene rubber (ABR), acrylonitrile-butadiene rubber, acrylic rubber, butyl rubber, fluororubber, polyethylene oxide, polyvinyl pyrrolidone, polypropylene, polyepichlorohydrin, polyphosphazene, ethylene propylene diene copolymer, polyvinyl pyridine, chlorosulfonated polyethylene, latex, polyester resin, acrylic resin, phenolic resin, epoxy resin, polyvinyl alcohol or a combination thereof.
[0041] In one or more embodiments, if an aqueous binder is used as the first binder and / or the second binder, the aqueous binder can be used together with a cellulose compound. The cellulose compound includes one or more of carboxymethyl cellulose, hydroxypropyl methylcellulose, methyl cellulose and an alkali metal salt thereof. The alkali metal can be Na, K and / or Li. If a cellulose compound is further used, the cellulose compound is also used as a binder, and therefore, the aqueous binder and the cellulose compound can be included together in the binder in each layer.
[0042] For example, if an aqueous binder and a cellulose compound are used in the binding layer, their amount may be about 10 wt % or less, or about 5 wt % to about 10 wt % based on a total of 100 wt % of the binding layer. If an aqueous binder and a cellulose compound are used in the negative electrode active material layer, their amount may be about 10 wt % or less, or about 5 wt % to about 10 wt % based on a total of 100 wt % of the negative electrode active material layer.
[0043] In one or more embodiments, the negative active material layer includes a Si-based active material and a carbon-based active material.
[0044] The carbonaceous anode active material can be crystalline carbon, amorphous carbon, or a combination thereof, and in one or more embodiments, can be crystalline carbon. Crystalline carbon can include natural graphite and / or artificial graphite having an indefinite shape, plate-like, flaky, spherical, and / or fibrous shape, or a combination thereof, and amorphous carbon can be soft carbon, hard carbon, mesophase pitch carbide, and / or sintered coke, etc.
[0045] The Si-based active material can be Si, Si-C composite, SiO x (0 < x < 2), Si-Q alloy (where Q is an element selected from alkali metals, alkaline earth metals, Group 13 elements, Group 14 elements, Group 15 elements, Group 16 elements, transition metals, rare earth elements, and combinations thereof, but not Si), or a combination thereof, or at least one of the above materials can be mixed with SiO2. The element Q can be selected from Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Tl, Ge, P, As, Sb, Bi, S, Se, Te, Po, and combinations thereof.
[0046] In one or more embodiments, the Si-based active material can be an Si-C composite.
[0047] The Si-C composite particles can have an average particle size D50 of, for example, about 0.5 μm to about 20 μm. According to one or more embodiments, the Si-C composite can include silicon particles and an amorphous carbon coating on the surface of the silicon particles. For example, it can include secondary particles (cores) formed by agglomeration of silicon primary particles and an amorphous carbon coating (shell) on the surface of the secondary particles. The amorphous carbon can be between the silicon primary particles, for example, to coat the silicon primary particles. For example, the amorphous carbon can exist as a coating on the silicon primary particles. The secondary particles can be presented by being distributed in the amorphous carbon matrix. For example, the silicon secondary particles can be dispersed in the amorphous carbon matrix.
[0048] The Si-C composite can also include crystalline carbon. For example, the Si-C composite can include a core containing crystalline carbon and silicon particles, and an amorphous carbon coating on the surface of the core. The crystalline carbon can be artificial graphite, natural graphite, or a combination thereof. The amorphous carbon can be soft carbon, hard carbon, mesophase pitch carbide, and / or sintered coke, etc.
[0049] If the Si-C composite includes silicon and amorphous carbon, based on 100 wt% in total of the Si-C composite, the amount of silicon may be from about 10 wt% to about 50 wt%, and the amount of amorphous carbon may be from about 50 wt% to about 90 wt%. In one or more embodiments, if the Si-C composite includes silicon, amorphous carbon, and crystalline carbon, based on 100 wt% in total of the Si-C composite, the amount of silicon may be from about 10 wt% to about 50 wt%, the amount of crystalline carbon may be from about 10 wt% to about 70 wt%, and the amount of amorphous carbon may be from about 20 wt% to about 40 wt%.
[0050] The amorphous carbon coating may have a thickness of from about 5 nm to about 100 nm. The silicon may include silicon particles (primary particles) that may have an average particle size D50 of from about 10 nm to about 1 μm, or from about 10 nm to about 200 nm. The silicon particles may include silicon (e.g., may include elemental silicon or may consist of silicon), a silicon alloy, and / or a silicon oxide form (e.g., silicon oxide). The silicon oxide may be represented by SiO x (0 < x < 2). The atomic weight ratio of Si:O representing the degree of oxidation may be from about 99:1 to about 33:67. In this specification, unless otherwise provided with a definition, the average particle size D50 represents the average particle size (D50) at which the cumulative volume in the particle size distribution is about 50 volume%.
[0051] In one or more embodiments, the mixing ratio of the Si-based active material and the carbon-based active material may be a weight ratio of from about 1:99 to about 99:1, from about 1:99 to about 50:50, or from about 5:95 to about 20:80.
[0052] If the Si-based active material and the carbon-based active material are used together as the negative electrode active material included in the negative electrode active material layer, a higher capacity can be obtained. In the negative electrode according to one or more embodiments, a bonding layer is included between the active material layer and the current collector. Therefore, even when using a Si-based active material that causes severe volume expansion during charging and discharging, separation of the active material layer during repeated charging and discharging cycles can be effectively suppressed or reduced. Therefore, according to the embodiments of the present disclosure, further improved cycle life characteristics can be obtained.
[0053] The negative electrode active material layer may include a negative electrode active material and a second binder, and may optionally further include a conductive material (e.g., an electrically conductive material). If the negative electrode active material layer includes a negative electrode active material and a second binder, the amount of the second binder may be about 3 wt% or less, or about 2 wt% to about 3 wt%, based on a total of 100 wt% of the negative electrode active material layer, and the amount of the negative electrode active material may be about 97 wt% or more, or about 97 wt% to about 98 wt%. In one or more embodiments, if the negative electrode active material layer includes a negative electrode active material, a second binder, and a conductive material, the amount of the second binder may be about 3 wt% or less, or about 2 wt% to about 3 wt%, based on a total of 100 wt% of the negative electrode active material layer, the amount of the negative electrode active material may be about 96 wt% or more, or about 96 wt% to about 97 wt%, and the amount of the conductive material may be about 1 wt% or less and greater than 0 wt%, for example, about 0.01 wt% to about 1 wt%.
[0054] The conductive material is included to provide electrode conductivity (e.g., electrical conductivity), and any suitable conductive material may be used as the conductive material unless it causes chemical changes (e.g., undesirable chemical changes in a rechargeable lithium battery), and examples of the conductive material may be: carbon-based materials such as natural graphite, artificial graphite, carbon black, carbon fibers, etc.; metal-based materials including metal powders and / or metal fibers of copper, nickel, aluminum, silver, etc.; conductive polymers such as polyphenylene derivatives; or mixtures thereof. Carbon black may be, for example, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal cracking black, or a combination thereof.
[0055] The current collector may include one selected from copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, a polymer substrate coated with a conductive metal (eg, an electrically conductive metal), and combinations thereof, but is not limited thereto.
[0056] If Figure 2 The negative electrode preparation according to one or more embodiments is performed as shown in , then the composition for the adhesive layer is coated on the current collector 3 and dried (step 1). The composition for the adhesive layer includes a carbon-based material, a first binder and a solvent. The solvent can be adjusted according to the type (or kind) of the first binder, and can be water, N-methylpyrrolidone or a combination thereof.
[0057] In the drying process, the bonding precursor layer 5A is prepared. The bonding precursor layer may be prepared to have a thickness of about 50 μm to about 150 μm, or about 70 μm to 120 μm.
[0058] Thereafter, some material may be peeled off from the bonding precursor layer to prepare a bonding layer 5 having a thickness of about 30 μm or less and / or having an interfacial bonding force of about 5 gf / mm or more (step 2 ).
[0059] The peeling process may be performed by attaching an adhesive tape to the adhesive precursor layer and peeling the adhesive tape, but the peeling process is not limited thereto. Any suitable process may be performed as long as it peels an appropriate amount of material from the adhesive precursor layer.
[0060] For example, the method using the adhesive tape can be performed by using a double-sided adhesive tape having an adhesive force of about 25 gf / mm or more and about 40 gf / mm or less, and peeling at a speed of about 100 mm / min. In one or more embodiments, the peeling process can be performed by steps such as using a blade and / or laser cutting.
[0061] exist Figure 2 In the figure, the surface of the adhesive layer is shown to be uneven, but this is only for clearly distinguishing the adhesive layer from the negative electrode active material layer, and is not limited to the shape of the surface of the adhesive layer having a set or predetermined roughness.
[0062] Subsequently, the negative electrode active material layer composition is coated on the binding layer and dried, and then pressed to prepare the negative electrode active material layer 7 (step 3). Coating, drying and pressing can be any suitable process for negative electrode preparation, and therefore, further description thereof is unnecessary here.
[0063] The negative electrode active material layer composition includes a negative electrode active material, a second binder, an optional conductive material (eg, an electrically conductive material) and a solvent. The solvent can be adjusted according to the type (or kind) of the second binder and can be water, N-methylpyrrolidone or a combination thereof.
[0064] Another embodiment provides a rechargeable lithium battery including a negative electrode, a positive electrode, and a non-aqueous binder.
[0065] The positive electrode may include a current collector and a positive active material layer on the current collector. The positive active material may include a compound capable of inserting and extracting lithium (lithiated insert compound). In some embodiments, at least one of a composite oxide selected from lithium and a metal selected from cobalt, manganese, nickel or a combination thereof may be used. For example, a compound represented by one of the following chemical formulas may be used. Li a A 1-b X b D 1 2 (0.90≤a≤1.8, 0≤b≤0.5); Li a A 1-b X b O 2-c1 D1 c1 (0.90≤a≤1.8,0≤b≤0.5,0≤c1≤0.05);Li a HAVE BEEN 1-b X b O 2-c1 D 1 c1 (0.90≤a≤1.8,0≤b≤0.5,0≤c1≤0.05);Li a HAVE BEEN 2-b X b O 4-c1 D 1 c1 (0.90≤a≤1.8,0≤b≤0.5,0≤c1≤0.05);Li a Ni 1-b- c Co b X c D 1 α (0.90≤a≤1.8,0≤b≤0.5,0≤c≤0.5,0<α≤2);Li a Ni 1-b-c Co b X c O 2-α T α (0.90≤a≤1.8,0≤b≤0.5,0≤c≤0.5,0<α<2);Li a Ni 1-b-c Co b X c O 2-α T2(0.90≤a≤1.8,0≤b≤0.5,0≤c≤0.5,0<α<2);Li a Ni 1-b-c Mr b X c D 1 α (0.90≤a≤1.8,0≤b≤0.5,0≤c≤0.5,0<α≤2);Li a Ni 1-b-c Mr b X c O 2-α T α (0.90≤a≤1.8,0≤b≤0.5,0≤c≤0.5,0<α<2);Li a Ni 1-b-c Mr b X c O 2-αT2 (0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.5, 0<α<2); Li a Ni b E c G d O2 (0.90≤a≤1.8, 0≤b≤0.9, 0≤c≤0.5, 0.001≤d≤0.1); Li a Ni b Co c L 1 d G e O2 (0.90≤a≤1.8, 0≤b≤0.9, 0≤c≤0.5, 0≤d≤0.5, 0≤e≤0.1); Li a NeG b O2 (0.90≤a≤1.8, 0.001≤b≤0.1) Li a CoG b O2 (0.90≤a≤1.8, 0.001≤b≤0.1); Li a Mn 1-b G b O2 (0.90≤a≤1.8, 0.001≤b≤0.1); Li a Mn b O4 (0.90≤a≤1.8, 0.001≤b≤0.1); Li a Mn 1-g G g PO4 (0.90≤a≤1.8, 0≤g≤0.5); QO2; QS2; LiQS2; V2O5; LiV2O5; LiZO2; LiNiVO4; Li (3-f) J2(PO4)3(0≤f≤2);Li (3-f) Fe2(PO4)3(0≤f≤2);Li a FePO4 (0.90≤a≤1.8).
[0066] In the above chemical formula, A is selected from Ni, Co, Mn or a combination thereof; X is selected from Al, Ni, Co, Mn, Cr, Fe, Mg, Sr, V, rare earth elements or a combination thereof; D 1 is selected from O, F, S, P or a combination thereof; E is selected from Co, Mn or a combination thereof; T is selected from F, S, P or a combination thereof; G is selected from Al, Cr, Mn, Fe, Mg, La, Ce, Sr, V or a combination thereof; Q is selected from Ti, Mo, Mn or a combination thereof; Z is selected from Cr, V, Fe, Sc, Y or a combination thereof; J is selected from V, Cr, Mn, Co, Ni, Cu or a combination thereof; L 1 Selected from Mn, Al or a combination thereof.
[0067] The compound may have a coating on the surface, or the compound may be mixed with another compound having a coating. The coating may include at least one coating element compound selected from the group consisting of an oxide of a coating element, a hydroxide of a coating element, an oxyhydroxide of a coating element, an oxycarbonate of a coating element, and a hydroxycarbonate of a coating element. The compound used for the coating may be amorphous and / or crystalline. The coating element included in the coating may include Mg, Al, Co, K, Na, Ca, Si, Ti, V, Sn, Ge, Ga, B, As, Zr, or a mixture thereof. The coating may be provided by using these elements in a compound in a manner that has no (or substantially no) adverse effect on the properties of the positive active material, for example, the method may include any suitable coating method (such as spraying and / or dipping, etc.), and therefore, further description thereof is unnecessary here.
[0068] In the positive electrode, the amount of the positive active material may be about 90 wt % to about 98 wt % based on the total weight of the positive active material layer.
[0069] In an embodiment, the positive active material layer may further include a binder and a conductive material (eg, an electrically conductive material), and may include the binder and the conductive material in an amount of about 1 wt % to about 5 wt % based on the total amount of the positive active material layer.
[0070] The binder improves the bonding performance between the positive electrode active material particles and the current collector. Examples of the binder may be polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin and / or nylon, but are not limited thereto.
[0071] The conductive material is included to provide electrode conductivity (e.g., electrical conductivity), and any suitable conductive material may be used as the conductive material unless it causes chemical changes (e.g., undesirable chemical changes in a rechargeable lithium battery). Examples of the conductive material may be: carbon-based materials such as natural graphite, artificial graphite, carbon black, carbon fibers, etc.; metal-based materials including metal powders and / or metal fibers of copper, nickel, aluminum, silver, etc.; conductive polymers such as polyphenylene derivatives; or mixtures thereof.
[0072] The current collector may include Al, but is not limited thereto.
[0073] The negative electrode and the positive electrode can be prepared by mixing an active material, a conductive material (e.g., an electrically conductive material) and a binder in a solvent to prepare an active material composition and coating the composition on a current collector. This electrode preparation can be any suitable electrode preparation used in the art, and therefore, further description thereof is unnecessary here. The solvent may be N-methylpyrrolidone or the like, but is not limited thereto. If an aqueous binder is used in the negative electrode, water can be used as a solvent for preparing the negative active material composition.
[0074] The electrolyte includes a nonaqueous organic solvent and a lithium salt.
[0075] The nonaqueous organic solvent serves as a medium for transporting ions participating in the electrochemical reaction of the battery.
[0076] The non-aqueous organic solvent may include carbonate solvents, ester solvents, ether solvents, ketone solvents, alcohol solvents and / or aprotic solvents. Carbonate solvents may include dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), ethyl methyl carbonate (MEC), ethylene carbonate (EC), propylene carbonate (PC) and / or butylene carbonate (BC), etc., and ester solvents may include methyl acetate, ethyl acetate, n-propyl acetate, dimethyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, decalactone, valerolactone, mevalonolactone and / or caprolactone, etc. Ether solvents may include dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, ethylene glycol dimethyl ether, 2-methyltetrahydrofuran, 2,5-dimethyltetrahydrofuran and / or tetrahydrofuran, etc., and ketone solvents may include cyclohexanone, etc. Alcohol solvents may include ethanol and / or isopropanol, etc., and aprotic solvents may include: nitriles (such as R-CN (wherein R is a C2 to C20 straight chain, branched or cyclic hydrocarbon group, and may include double bonds, aromatic rings and / or ether bonds, etc.)); amides (such as dimethylformamide); dioxolanes (such as 1,3-dioxolane and / or 1,4-dioxolane, etc.); and / or sulfolane, etc.
[0077] The organic solvent may be used alone or in a mixture. If the organic solvent is used in a mixture, the mixing ratio may be controlled according to suitable or desired battery performance, and may be any suitable one used in the related art.
[0078] If a non-aqueous organic solvent is mixed and used, a mixed solvent of a cyclic carbonate and a chain carbonate, a mixed solvent of a cyclic carbonate and a propionate solvent, or a mixed solvent of a cyclic carbonate, a chain carbonate and a propionate solvent can be used. The propionate solvent can be methyl propionate, ethyl propionate, propyl propionate or a combination thereof.
[0079] If cyclic carbonate and chain carbonate, or cyclic carbonate and propionate solvent are mixed together, they can be mixed together in a volume ratio of about 1:1 to about 1:9, so the performance of the electrolyte can be improved. If cyclic carbonate, chain carbonate and propionate solvent are mixed together, they can be mixed together in a volume ratio of about 1:1:1 to about 3:3:4. The mixing ratio of the solvent can be appropriately or properly adjusted according to the appropriate or desired properties.
[0080] The non-aqueous organic solvent may further include an aromatic hydrocarbon solvent and a carbonate solvent. The carbonate solvent and the aromatic hydrocarbon solvent may be mixed together in a volume ratio of about 1:1 to about 30:1.
[0081] The aromatic hydrocarbon organic solvent may be an aromatic hydrocarbon compound represented by Chemical Formula 1.
[0082] Chemical formula 1 In Chemical Formula 1, R1 to R6 are the same or different and are selected from hydrogen, halogen, C1 to C10 alkyl, halogenated alkyl, and combinations thereof.
[0083] Examples of aromatic hydrocarbon organic solvents include benzene, fluorobenzene, 1,2-difluorobenzene, 1,3-difluorobenzene, 1,4-difluorobenzene, 1,2,3-trifluorobenzene, 1,2,4-trifluorobenzene, chlorobenzene, 1,2-dichlorobenzene, 1,3-dichlorobenzene, 1,4-dichlorobenzene, 1,2,3-trichlorobenzene, 1,2,4-trichlorobenzene, iodobenzene, 1,2-diiodobenzene, 1,3-diiodobenzene, 1,4-diiodobenzene, 1,2,3-triiodobenzene, 1,2,4-triiodobenzene, toluene, fluorobenzene, Toluene, 2,3-difluorotoluene, 2,4-difluorotoluene, 2,5-difluorotoluene, 2,3,4-trifluorotoluene, 2,3,5-trifluorotoluene, chlorotoluene, 2,3-dichlorotoluene, 2,4-dichlorotoluene, 2,5-dichlorotoluene, 2,3,4-trichlorotoluene, 2,3,5-trichlorotoluene, iodotoluene, 2,3-diiodotoluene, 2,4-diiodotoluene, 2,5-diiodotoluene, 2,3,4-triiodotoluene, 2,3,5-triiodotoluene, xylene or a combination thereof.
[0084] The electrolyte may further include vinylethyl carbonate, vinylene carbonate, and / or a vinyl carbonate-based compound represented by Chemical Formula 2 as an additive for improving cycle life.
[0085] Chemical formula 2 In Chemical Formula 2, R7 and R8 are the same or different and may be independently hydrogen, halogen, cyano (CN), nitro (NO2) or C1 to C5 fluoroalkyl, provided that at least one selected from R7 and R8 is halogen, cyano (CN), nitro (NO2) or C1 to C5 fluoroalkyl, and R7 and R8 are not hydrogen at the same time.
[0086] Examples of vinyl carbonate compounds may include difluoroethylene carbonate, chloroethylene carbonate, dichloroethylene carbonate, brominated vinyl carbonate, dibromoethylene carbonate, nitroethylene carbonate, cyanoethylene carbonate, and / or fluoroethylene carbonate, etc. In embodiments where additives are used to improve cycle life, the amount of the additive may be suitably controlled within a suitable or appropriate range.
[0087] Lithium salts dissolved in organic solvents supply lithium ions to the battery, fundamentally operate rechargeable lithium batteries, and improve the transport of lithium ions between the positive electrode and the negative electrode. Examples of lithium salts include those selected from LiPF6, LiBF4, LiSbF6, LiAsF6, LiN(SO2C2F5)2, Li(CF3SO2)2N, LiN(SO3C2F5)2, Li(FSO2)2N (lithium bis(fluorosulfonyl)imide: LiFSI), LiC4F9SO3, LiClO4, LiAlO2, LiAlCl4, LiPO2F2, LiN(C x F 2x+1 SO2)(C y F 2y+1 SO2) (wherein x and y are integers from 1 to 20), lithium difluoro(bis(oxalato)phosphate), LiCl, LiI, LiB(C2O4)2 (lithium bis(oxalato)borate: LiBOB) and lithium difluoro(oxalato)borate (LiDFOB) as a supporting electrolyte salt. The concentration of the lithium salt may be in the range of about 0.1 M to about 2.0 M. If the lithium salt is included in the above concentration range, the electrolyte may have excellent performance and lithium ion mobility due to suitable or optimal electrolyte conductivity and viscosity.
[0088] According to the type (or kind) of the rechargeable lithium battery, the separator may be between the positive electrode and the negative electrode. The separator may use polyethylene, polypropylene, polyvinylidene fluoride or a multilayer having two or more layers thereof, and may be a mixed multilayer (such as a polyethylene / polypropylene double-layer separator, a polyethylene / polypropylene / polyethylene three-layer separator, and / or a polypropylene / polyethylene / polypropylene three-layer separator, etc.).
[0089] The diaphragm may include a porous substrate and a coating including a ceramic on at least one side of the porous substrate. The ceramic may include SiO2, Al2O3, Al(OH)3, AlO(OH), TiO2, BaTiO2, ZnO2, Mg(OH)2, MgO, Ti(OH)4, ZrO2, aluminum nitride, silicon carbide, boron nitride, or a combination thereof.
[0090] According to one or more embodiments, the diaphragm may include a composite porous diaphragm including a porous substrate and a functional layer on the porous substrate of the composite porous diaphragm. The functional layer may have additional functions, for example, may be selected from at least one of a heat-resistant layer and an adhesive layer. The heat-resistant layer may include a heat-resistant resin and an optional filler. The adhesive layer may include an adhesive resin and an optional filler. The filler may be an organic filler, an inorganic filler or a combination thereof. The heat-resistant resin, the adhesive and the filling resin may be any suitable material that can be used for the diaphragm in the related art.
[0091] Rechargeable lithium batteries can be classified into lithium ion batteries, lithium ion polymer batteries or lithium polymer batteries according to the types (or kinds) of separators and electrolytes, can be classified into cylindrical, prismatic, coin or pouch types according to the shapes of the rechargeable lithium batteries, and can be classified into block type (or type) or thin film type (or type) according to the sizes of the rechargeable lithium batteries. The structure and manufacture of such batteries can be any suitable structure and manufacture used in the related art, and therefore, further description thereof is unnecessary here.
[0092] Figure 3 is an exploded perspective view of a rechargeable lithium battery according to one or more embodiments. The rechargeable lithium battery according to one or more embodiments is shown as a prismatic battery, but is not limited thereto and may include batteries of various shapes such as a cylindrical battery, a pouch battery, and the like.
[0093] refer to Figure 3 , a rechargeable lithium battery 100 according to one or more embodiments may include an electrode assembly 40 manufactured by winding a positive electrode 10, a negative electrode 20, and a separator 30 between the positive electrode 10 and the negative electrode 20, and a case 50 accommodating the electrode assembly 40. The positive electrode 10, the negative electrode 20, and the separator 30 may be immersed in an electrolyte.
[0094] Hereinafter, examples of embodiments of the present disclosure and comparative examples are described. However, these examples are not to be construed as limiting the scope of the present disclosure in any sense. The negative electrodes in the examples and comparative examples are based on a battery having a capacity of 5.8 mAh / cm 2 The negative electrode is designed and prepared for a current density of .
[0095] Example 1 95 wt % of artificial graphite, 1 wt % of carboxymethyl cellulose, and 4 wt % of a styrene-butadiene rubber binder were mixed together in water to prepare an adhesive layer composition.
[0096] 91.5 wt % of artificial graphite, 6 wt % of silicon-carbon composite, 1 wt % of carboxymethyl cellulose, and 1.5 wt % of styrene-butadiene rubber were mixed together in a water solvent to prepare a negative active material layer slurry.
[0097] The silicon-carbon composite includes a core containing silicon nanoparticles and a soft carbon coating on the surface of the core. Based on the total amount of the silicon-carbon composite, the amount of the silicon nanoparticles is 40wt%, and the amount of amorphous carbon is 60wt%. The thickness of the soft carbon coating is 20nm, and the silicon nanoparticles have an average particle size (D50) of 100nm.
[0098] The adhesion layer composition was coated on a Cu current collector and dried to prepare an adhesion precursor layer having a thickness of 80 μm.
[0099] An adhesive tape having an adhesive force of 32 gf / mm was attached to the adhesive precursor layer and peeled at a speed of 100 mm / min under a 180 degree (°) peel test method using a tensile tester to form an adhesive layer having a thickness of 21 μm.
[0100] The negative electrode active material layer slurry is coated on the binding layer and dried, and then pressed to prepare a negative electrode active material layer, thereby obtaining a negative electrode.
[0101] In the prepared negative electrode, the thickness of the binding layer was 21 μm, and the thickness of the negative electrode active material layer was 64 μm. The active mass density of the negative electrode active material layer was 1.59 g / cm 2 .
[0102] Example 2 A negative electrode was prepared by substantially the same steps as in Example 1 except that an adhesive tape having an adhesive force of 27 gf / mm was attached and peeled off by substantially the same steps to prepare an adhesive layer having a thickness of 29 μm and an active material layer having a thickness of 62 μm.
[0103] Example 3 A negative electrode was prepared by substantially the same steps as those in Example 1, except that a bonding layer composition was prepared by mixing 93 wt % of artificial graphite, 1 wt % of carboxymethyl cellulose, and 6 wt % of a styrene-butadiene rubber binder in an aqueous solvent. In the prepared negative electrode, the thickness of the bonding layer was 21 μm, and the thickness of the negative active material layer was 62 μm.
[0104] Example 4 A negative electrode was prepared by steps substantially the same as those of Example 3, except that 89.5 wt % of artificial graphite, 8 wt % of the silicon-carbon composite used in Example 1, 1 wt % of carboxymethyl cellulose and 1.5 wt % of styrene-butadiene rubber were mixed together in an aqueous solvent to prepare a negative active material layer slurry, and a bonding layer having a thickness of 21 μm and an active material layer having a thickness of 60 μm were prepared.
[0105] Example 5 91 wt % of artificial graphite, 1 wt % of carboxymethyl cellulose, and 8 wt % of a styrene-butadiene rubber binder were mixed together in water to prepare an adhesive layer composition.
[0106] 87.5wt% of artificial graphite, 10wt% of the silicon-carbon composite used in Example 1, 1wt% of carboxymethyl cellulose and 1.5wt% of styrene-butadiene rubber were mixed together in an aqueous solvent to prepare a negative electrode active material layer slurry. The adhesive layer composition and the negative electrode active material layer slurry were used to prepare an adhesive layer having a thickness of 23μm and an active material layer having a thickness of 54μm, thereby preparing a negative electrode by substantially the same steps as those in Example 3.
[0107] Comparative Example 1 91.5 wt % of artificial graphite, 6 wt % of the silicon-carbon composite used in Example 1, 1 wt % of carboxymethyl cellulose, and 1.5 wt % of styrene-butadiene rubber were mixed together in a water solvent to prepare a negative active material layer slurry.
[0108] The negative electrode active material layer slurry was coated on a Cu foil current collector, dried and pressed to prepare a negative electrode active material layer, thereby preparing a negative electrode. In the prepared negative electrode, the thickness of the negative electrode active material layer was 91 μm. The active mass density of the negative electrode active material layer was 1.60 g / cm 2 .
[0109] Comparative Example 2 89 wt % of artificial graphite, 6 wt % of silicon-carbon composite, 1 wt % of carboxymethyl cellulose, and 4 wt % of styrene-butadiene rubber were mixed together in a water solvent to prepare a first negative active material layer slurry.
[0110] 91.5 wt % of artificial graphite, 6 wt % of silicon-carbon composite, 1 wt % of carboxymethyl cellulose, and 1.5 wt % of styrene-butadiene rubber were mixed together in a water solvent to prepare a second negative active material layer slurry.
[0111] The silicon-carbon composite comprises a core comprising silicon nanoparticles and a soft carbon coating on the surface of the core. Based on the total amount of the silicon-carbon composite, the amount of the silicon nanoparticles is 40wt%, and the amount of amorphous carbon is 60wt%. The thickness of the soft carbon coating is 20nm, and the silicon nanoparticles have an average particle size D50 of 100nm.
[0112] The first negative active material layer slurry was coated on a Cu current collector and dried to prepare a first negative active material layer.
[0113] The second negative electrode active material layer slurry is coated on the first negative electrode active material layer, dried and pressurized to prepare the second negative electrode active material layer, thereby preparing a negative electrode.
[0114] In the prepared negative electrode, the thickness of the first negative electrode active material layer was 48 μm, and the thickness of the second active material layer was 44 μm. The active mass density of the second negative electrode active material layer was 1.59 g / cm 2 .
[0115] Comparison Example 3 95 wt % of artificial graphite, 1 wt % of carboxymethyl cellulose, and 4 wt % of styrene-butadiene rubber were mixed together in a water solvent to prepare a first negative active material layer slurry.
[0116] 91.5wt% of artificial graphite, 6wt% of silicon-carbon composite, 1wt% of carboxymethyl cellulose and 1.5wt% of styrene-butadiene rubber were mixed together in an aqueous solvent to prepare a second negative active material layer slurry. A first negative active material having a thickness of 59μm and a second negative active material layer having a thickness of 46μm were prepared using the active material slurry using substantially the same steps as those in Comparative Example 2, thereby preparing a negative electrode.
[0117] Experimental Example 1: Evaluation of interfacial adhesion The interfacial adhesion between the current collectors and the coating layers of Examples 1 to 5 was evaluated by using a tensile tester (available from SHIMADZU Corporation) according to a 90 degree (°) peel test method at 100 mm / min. The interfacial adhesion between the current collector of Comparative Example 1 and the active material layer and the interfacial adhesion between the current collectors of Comparative Examples 2 and 3 and the first negative active material were measured.
[0118] The results are shown in Table 1.
[0119] Experimental Example 2: Evaluation of Interface Resistance Characteristics The resistance of the electrodes according to Examples 1 to 5 and Comparative Examples 1 to 3 was measured five times using a 46-pin resistance meter (available from HIOKI, Co., Ltd.), respectively, with the measurement standard set to 10 mA and 10Ω. The average values of the measured values are shown in Table 1.
[0120] Experimental Example 3: Evaluation of ionic impedance characteristics The electrodes of Examples 1 to 5 and Comparative Examples 1 to 3 were cut horizontally into 2.5 cm and vertically into 4 cm, respectively, and then a symmetrical battery was manufactured by using the same electrodes. Ionic impedance was measured. The results are shown in Table 1.
[0121] Table 1 As shown in Table 1, Examples 1 to 5 including an adhesive layer including 90 wt % or more of a carbon-based material between a current collector and a negative active material layer exhibited excellent interfacial adhesive forces of 5.15 gf / mm or more, 0.33×10 -2 * Ωcm 2 or lower low interface resistance and 27.9Ωcm 2 or lower low ionic resistance.
[0122] Comparative Example 1, which does not include an adhesive layer, exhibits extremely low interfacial adhesion and excellent interfacial resistance and ionic impedance.
[0123] Comparative Examples 2 and 3, which did not include an adhesive layer and two negative active material layers, showed slightly increased adhesive force (which was still lower than that of the example) and high ionic resistance.
[0124] Although the subject matter of the present disclosure has been described in conjunction with what are presently considered to be practical example embodiments, it will be understood that the present disclosure is not limited to the disclosed embodiments, but on the contrary, is intended to cover various modifications and equivalent arrangements included within the spirit and scope of the appended claims and their equivalents. Therefore, the above-described embodiments should be understood as examples and not to limit the present disclosure in any way.
Claims
1. A negative electrode for a rechargeable lithium battery, the negative electrode comprising: current collector; A negative electrode active material layer; as well as an adhesive layer between the current collector and the negative electrode active material and having a thickness of 30 μm or less, Wherein, the adhesive layer includes the carbon-based material in an amount of 90 wt % or more based on 100 wt % in total of the adhesive layer.
2. The negative electrode for a rechargeable lithium battery according to claim 1, wherein The carbon-based material includes crystalline carbon, amorphous carbon or a combination thereof.
3. The negative electrode for a rechargeable lithium battery according to claim 1, wherein The negative electrode active material layer includes Si-based active materials and carbon-based active materials.
4. The negative electrode for a rechargeable lithium battery according to claim 1, wherein The adhesive layer has a thickness of 10 μm to 30 μm.
5. The negative electrode for a rechargeable lithium battery according to claim 1, wherein The adhesive layer comprises a first binder, and The negative electrode active material layer includes a second binder.
6. A negative electrode for a rechargeable lithium battery, the negative electrode comprising: current collector; A negative electrode active material layer; as well as An adhesive layer is provided between the current collector and the negative electrode active material. Wherein, the interfacial adhesion between the adhesive layer and the current collector is 5 gf / mm or greater.
7. The negative electrode for a rechargeable lithium battery according to claim 6, wherein The interfacial adhesion between the adhesive layer and the current collector is 5 gf / mm to 10 gf / mm.
8. The negative electrode for a rechargeable lithium battery according to claim 6, wherein The negative electrode active material layer includes a Si-based active material and a carbon-based active material.
9. The negative electrode for a rechargeable lithium battery according to claim 6, wherein The adhesive layer has a thickness of 10 μm to 30 μm.
10. The negative electrode for a rechargeable lithium battery according to claim 6, wherein The adhesive layer includes a first adhesive, and The negative electrode active material layer includes a second binder.
11. The negative electrode for a rechargeable lithium battery according to claim 1 or 6, wherein: The negative electrode active material layer has a thickness of 30 μm to 120 μm.
12. The negative electrode for a rechargeable lithium battery according to claim 5 or 10, wherein An amount of the first binder is 10 wt % or less based on 100 wt % in total of the adhesive layer.
13. The negative electrode for a rechargeable lithium battery according to claim 12, wherein An amount of the first binder is 3 wt % to 10 wt % based on 100 wt % in total of the adhesive layer.
14. The negative electrode for a rechargeable lithium battery according to claim 5 or 10, wherein: The amount of the second binder is 3 wt % or less based on 100 wt % in total of the negative active material layer.
15. The negative electrode for a rechargeable lithium battery according to claim 14, wherein The amount of the second binder is 1 wt % to 3 wt % based on 100 wt % of the total amount of the negative active material layer.
16. The negative electrode for a rechargeable lithium battery according to claim 5 or 10, wherein: Based on 100 wt % of the total of the negative electrode active material layer and the binding layer, The amount of the first binder is 1 wt % or more and 5 wt % or less.
17. The negative electrode for a rechargeable lithium battery according to claim 5 or 10, wherein: Based on 100 wt % of the total of the binding layer and the negative electrode active material layer, The amount of the second binder is 1 wt % or more and 2.4 wt % or less.
18. The negative electrode for a rechargeable lithium battery according to claim 1 or 6, wherein: The adhesive layer is prepared by coating an adhesive layer composition on the current collector and drying it to prepare an adhesive precursor layer, and partially peeling off the adhesive precursor layer.
19. The negative electrode for a rechargeable lithium battery according to claim 5 or 10, wherein: The first binder and the second binder are the same as or different from each other.
20. A rechargeable lithium battery, comprising: The negative electrode according to any one of claims 1 to 10; Positive electrode; as well as Non-aqueous electrolytes.